HALLYU DI TANAH MELAYU (Cultural Studies pada Korean Lovers di Pekanbaru) - Raja Widya Novchi (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Darma Agung, 2020)
The majority of Pekanbaru City's population is Malay and highly upholds customs. In the midst of the incessant Riau Malay Customary Institution (LAM) in launching local culture learning, there is a group of young people who uphold and develop foreign culture, namely Korean pop culture (Hallyu). This study discusses the behavior of adolescent hallyu fans using qualitative ethnographic methods of data collection in the form of in-depth interviews with 5 informants, observation and documentation. The results of the ethnographic study found that (1) Attention, watching Korean drama series, watching reality / variety shows, following idol social media and seeing concerts (2) Retention, the ability of adolescents to recall what has been noticed from mass media and the internet (3) Reproduction , community members usually use Hangul / Korean when communicating, change their nicknames with Korean names, eat Korean food, buy Korean products such as gadgets, bags, hats, idol artist photo albums, merchandise and participate in dance cover competitions and Korean-style sing covers (4) Motivation, there is a place to gather with fellow fans of Korean culture, namely the establishment of a Korean Lovers community in Pekanbaru, a community family gathering activity that makes them more compact and motivates teenagers to develop hallyu.